Efecto de algunas características anatómicas sobre el módulo de elasticidad dinámico en clones de Eucalyptus - Bulman Hartkopf, Christian; Winck, Rosa Ángela; Paiva González, Karen Belén; Fassola, Hugo Enrique; Stefani, Pablo Marcelo (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM); EEA Montecarlo, INTA, 2023)
Anatomical characteristics of five Eucalyptus clones, fiber length, fiber wall thickness and microfibrillar angle, were determined and compared with basic density, speed of sound and the dynamic modulus of elasticity in logs. Speed of sound and dynamic modulus of elasticity values were measured by acoustic resonance. The results showed that only fiber wall thickness explains basic density, and that there is a negative and significant correlation between microfibrillar angle and fiber length. In addition, these latter variables better describe speed of sound and dynamic modulus of elasticity than fiber wall thickness. Statistical differences were found between the genetic materials for all variables analyzed.